Parametric Optimization and Determination of a Suitable Welding Process for Stainless Steel-Mild Steel Dissimilar Metals Weld - Sada, S. O.; Enyi, L. C. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Difficulties associated with dissimilar metals welding differ remarkably and can be minimized with the selection of a suitable joining process, modification of the joining technique, and the adoption of optimal process parameters. This study investigates the suitability of three fusion welding processes (gas tungsten arc welding (GTAW), gas metal arc weld (GMAW), and shielded metal arc welding (SMAW)) in the welding of stainless steel to mild steel plates based on their mechanical properties and observed weld defects. Gas tungsten arc welding (GTAW) process which turned out to be the most suitable of the three, recording the least imperfections, an efficiency in mechanical properties of 8% higher compared to the other processes, furthermore analyzed using the response surface methodology (RSM) to obtain a models of the input and output relationship, as well as the optimal process parameters was conducted. An optimal parameters of 461.88N/mm2 for the tensile strength and 31.65% for the Elongation was observed at the combined input parameters of 200 amp, 15 volt, 20 l/min, and 2.4mm for the weld current, arc voltage, gas flow rate and filler rod respectively. Therefore, the application of optimal process parameters along with a compatible weld process is recommended in the welding of dissimilar metals to guarantee excellent weld qualities.